Identifikasi Faktor yang Mempengaruhi Keberhasilan Pengobatan Penderita Tuberkulosis di Kabupaten Bima 2014-2016 - Sahril Ramadhan; Yanri Wijayanti Subroto; Ari Probandari (Media Penelitian dan Pengembangan Kesehatan, 2019)
Abstract Tuberculosis is the world health problems. Indonesia is the second largest country with TB sufferers after India. The treatment success rate atBima District in 2016 was 89.10%. The aim of the study was to find out the determinants of the successful treatment of tuberculosis patients in Bima District. This study is an analytical using a retrospective cohort design. The population is all TB patient in Bima District. The independent variables are gender, age, distance of the house, anatomic location of the disease, history of previous treatment and the basis of diagnosis. The dependent variable is the success of treatment consisting of recovery and complete treatment. Data was obtained from the TB register secondary data TB.03 Bima District Health Office. Chi-square and Fisher exact test was employed for data analysis. Obtained 1,402 TB sufferers , 1,232 TB patients data included in the study analysis with an average ≥ 15 years as many as 1198 (97%), and 803 (65%) were men. A total 1,154 (94%) entered the definition of successful treatment. The success of treatment for TB patients is influenced by gender (RR:1.016; CI 95%:0.987 to 1.046; p=0.369) and age (RR:1.070; CI 95%:1.054 to 1.086; p=0.163) but statistically insignificant. Distance of houses with health facilities (RR:0.962; CI 95%:0.995 to 0.930; p=0.139), anatomic location of disease (RR :0.934; CI 95%:0.920 to 0.948; p=0.109), previous treatment history (RR:0.998; CI 95%:0.936 to 1.064; p=1.00), basic diagnosis (RR:0.935; CI 95%:0.922 to 0.949; p=0.399) did not affect the success of TB treatment and statistically insignificant. There are no factors that proved to significantly be the deciding factor for the success of the treatment of TB. Abstrak Tuberkulosis (TB) merupakan masalah kesehatan dunia. Indonesia merupakan negara dengan penderita TB terbanyak kedua setelah India. Angka keberhasilan pengobatan TB di Kabupaten Bima pada tahun 2016 adalah 89,10%. Tujuan penelitian untuk mengetahui faktor determinan keberhasilan pengobatan penderita TB di Kabupaten Bima. Penelitian ini merupakan penelitian analitik dengan menggunakan desain kohort retrospektif. Populasi adalah seluruh penderita TB di Kabupaten Bima. Variabel bebas yaitu jenis kelamin, usia, jarak rumah, lokasi anatomi penyakit, riwayat pengobatan sebelumnya, dan dasar diagnosis. Variabel terikat adalah keberhasilan pengobatan terdiri atas sembuh dan pengobatan lengkap. Data diperoleh dari data sekunder register TB.03 Dinas Kesehatan Kabupaten Bima. Analisis data dengan univariat, bivariat dengan uji Chi-square dan fisher exact test. Didapatkan 402 Penderita TB, 1.232 data pasien masuk dalam analisis penelitian dengan usia rata-rata ≥15 tahun 1.198 (97%), dan 803 (65%) adalah laki-laki. Sebanyak 1.154 orang (94%) masuk dalam definisi berhasil pengobatan. Keberhasilan pengobatan penderita TB dipengaruhi oleh jenis kelamin (RR=1,016; CI 95%:0,987-1,046; p=0,369) dan usia (RR=1,070; CI 95%:1,054-1,086; p=0,163) tetapi secara statistik tidak signifikan. Jarak rumah dengan fasilitas pelayanan kesehatan (RR=0,962; CI 95%:0,930-0,995; p=0,139), lokasi anatomi penyakit (RR=0,934; CI 95%:0,920-0,948; p=0,109), riwayat pengobatan sebelumnya (RR=0,998; CI 95%:0,9361,064; p=1,00), dasar diagnosis (RR=0,935; CI 95%:0,922-0,949; p=0,399) tidak mempengaruhi keberhasilan pengobatan TB dan secara statistik tidak signifikan. Tidak ada faktor yang terbukti secara signifikan menjadi faktor penentu bagi keberhasilan pengobatan TB.